The development of synchronous text-based instant messaging as an online interviewing tool - Pearce, G.; Thøgersen-Ntoumani, Cecilie; Duda, J. (Routledge, 2014)
The article reports the development of a synchronous text-based online interviewing tool with a continuity of private discussion that is not achieved in open-ended questionnaires, email interviews and online discussion boards. The participants were women who had undergone a surgical or natural menopause, who in a pilot interview highlighted the potential sensitivity of this subject and inspired the implementation of this method. The overall feedback was positive with the main advantages centred on feelings of anonymity, convenience and a more comfortable interview environment. Disadvantages included lack of body language and technical issues with computers. This technique ensures a degree of confidentiality while still obtaining depth of enquiry, where other qualitative methods potentially risk invading a participant’s privacy. It can be offered both alongside other interviewing techniques to allow participant choice and on its own when exploring sensitive and personal topics or when extra participant anonymity is appropriate.